Humoral immune response of Salmonella typhimurium and Salmonella enteritidis sonicated antigens in rabbits: AL-Samarrae. E.A.A.., AL-Shawi, A.M.A. and AL-Taiy, H.S.R. - Al-Samarrae, Ekram A. (The Iraqi Journal of Veterinary Medicine, 2012)
Salmonella typhimurium and salmonella enteritidis were isolated from infected goat andprepared an antigens of whole cell sonicated antigen of S.typhimurium(WCS.Ag.S.typhimurium ),whole cell sonicated antigen of S.enteritidis (WCS.Ag.S.entertidis) and combination of whole cell sonicated antigen (Salmonella typhimurium andSalmonella enteritidis) (CWS.Ag) . Their efficacy was evaluated by using tube agglutinationtest and enzyme linked immune sorbent assay (ELISA). Twenty rabbits were randomlydivided into four groups; the 1st group was immunized by WCS. Ag - Salmonella enteritidis,2nd group immunized by (WCS Ags .typhimurium), 3rd group immunized by CWCS.Agcompound and 4th left as control group which injected by physiological buffer saline (pH7.2). The antibody titer was increased in after the day 12, first, second and third months ofimmunization by agglutination test. IgG concentration was done by ELISA at the same time;which were recorded a higher significant differences (p˂ 0.01) at the first month in the groupimmunized by CWS Ag (449.65 ±38.6 1ng/ml IgG and 952± 20.85 antibodies titer )compared with other immunized groups ( WCS – Ag – S. enteritidis andWCS.Ag.S.typhimurium ). Also, the IgG concentration and antibodies titer are still higher inthe second and the third months in the immunized group by CWCS.Ag. 218.90± 6.69ng/ml,528± 68.58 and 89.55± 2.63ng/ml, 280± 49.98 respectively with significant differences (p˂0.01) compared with the immunized groups (WCS.Ag.S. entertidis and WCS. Ag.S.typhimurium) and also, they are significant (p˂ 0.01) when compared with the control groupResearch